Effects of waste milk feeding on rumen fermentation and bacterial community of pre-weaned and post-weaned dairy calves - Zhang, Xinyue; Cheng, Chuanteng; Lv, Jingyi; Bai, Haixin; Sun, Fang; Liu, Chundong; Liu, Chunlong; Zhang, Yonggen; Xin, Hangshu (Frontiers in Microbiology, 2023)
Abstract The objective of this study was to investigate the effect of waste milk with antibiotic residue on rumen fermentation and rumen bacterial composition of dairy calves during the preweaned and postweaned periods. A total of 24 Holstein male calves (43.4 ± 0.93 kg body weight, mean ± standard error) were allocated into 4 blocks based on arrival date according to a completely randomized block design. Animals were fed 4 L of whole milk twice a day after successful transfer of passive immunity until 7 d of age. From 8–56 d of age, calves were supplied 100% milk replacer (MR, n = 8), 50% milk replacer mixed with 50% waste milk (MM, n = 8), or 100% waste milk (WM, n = 8). Starter and fresh water were offered ad libitum throughout the experiment. Ruminal liquid samples were collected at 49 and 63 d of age and then subjected to pH, VFA, NH3-N and 16S rRNA gene amplicon sequencing. The results showed that feeding WM had no effect on the pH value or the concentrations of acetic acid, propionic acid, butyric acid, isovaleric acid, valeric acid, total VFA or NH3-N in dairy calves compared to milk replacer. However, from 49 d to 63 d of age, the pH value (P < 0.001) was significantly increased, while the levels of total VFA (P = 0.004), acetic acid (P = 0.01), propionic acid (P = 0.003) and valeric acid (P < 0.001) were significantly decreased. For rumen microorganisms, there was no difference in bacterial diversity among the three treatments. A difference in the relative abundance of Veillonellaceae was observed between the MR and WM groups (P = 0.05), and it was significantly lower in the WM group than in the MR group at 49 d of age; however, no difference was detected until 63 d of age. Analysis of temporal changes in rumen bacteria based on α-diversity and β-diversity as well as the relative abundance of the top 5 phyla, top 10 families, and top 20 genera between 49 and 63 d of age did not exhibit any difference.